FORWARD AND BACKWARD STATIC ANALYSIS FOR CRITICAL NUMERICAL ACCURACY IN FLOATING POINT PROGRAMS - Kanagasabapathi, Somasundaram; Thushara, MG (Computer Science, 2020)
In this article, we introduce a new static analysis for numerical accuracy. Weaddress the problem of determining the minimal accuracy on the inputs and on the intermediary results of a program containing  foating-point computations in order to ensure a desired accuracy on the outputs. The main approach is to combine a forward and a backward static analysis, done by abstract interpretation. The backward analysis computes the minimal accuracy needed for the inputs and intermediary results of the program in order to ensure a desired accuracy on the results, specied by the user. In practice, the information collected by our analysis may help to optimize the formats used to represent the values stored in the variables of the program or to select the appropriate sensors. To illustrate our analysis, we have shown a prototype example with experimental results.